PENGARUH PERSEPSI KONTROL PERILAKU, PENGETAHUAN PAJAK DAN PERSEPSI KEADILAN PAJAK TERHADAP KEPATUHAN WAJIB PAJAK - Abdul Basit (TEKUN: Jurnal Telaah Akuntansi dan Bisnis, 2014)
This research aims to analyze the factors that influence taxpayer compliance people doing free work or business activities in fulfilling the obligations of their tax. This research consists of three independent variables and the one dependent variable. The independent variable in this research is the perception of control behavior, tax knowledge and tax fairness perception. While the dependent variable in this study is the tax compliance. This research uses techniques of convenience sampling with a number of sample as much as 178 respondents and survey with questionnaire method in the collection of the data. Respondents who were sampled in this study are the tax payers private person who did free work or business activities registered in the Tax Services Office of Jakarta Matraman, Tax Service Office of Jakarta Duren Sawit, Tax Service Office of Jakarta Jatinegara, and Tax Services Office of Jakarta Kramat Jati. The analysis of research data analysis using Structural Equation Modeling (SEM) variance-based or so-called Component Based SEM by using SmartPLS software version 2.0 Based on the results of the data processing and analysis of the research that has been done shows that the perception of control doesn’t affect behavior significantly to tax compliance, tax knowledge influence significantly to perceptions of tax fairness and tax compliance and tax fairness perceptions influence significantly to tax compliance. Keywords: Tax Compliance, the perception of control behavior, tax knowledge and perception of tax fairness.